A survey of hidden-variables theories - Belinfante, F. J. (Frederik Jozef) (International series of monographs in natural philosophy, 1973)
A Survey of Hidden-Variables Theories is a three-part book on the hidden-variable theories, referred in this book as ""theories of the first kind"". Part I reviews the motives in developing different types of hidden-variables theories. The quest for determinism led to theories of the first kind; the quest for theories that look like causal theories when applied to spatially separated systems that interacted in the past led to theories of the second kind. Parts II and III further describe the theories of the first kind and second kind, respectively